Analisis Parameter Seismisitas a-Value dan b-Value serta Percepatan Tanah Maksimum (PGA) Sebelum dan Sesudah Gempa Ambon 2019 Menggunakan Metode Probabilistic Seismic Hazard Analysis (PSHA) - Indah Putri Utami; Dwi Pujiastuti (Universitas Andalas, 2024)
Probabilistic Seismic Hazard Analysis (PSHA) is a method to estimate earthquake risk in a region by considering uncertainties in earthquake sources and local ground response. To estimate earthquake risk and seismic impacts in a region, an in-depth analysis of seismicity parameters, such as a-value and b-value, as well as maximum ground acceleration (PGA), is required. This study aims to analyze changes in seismicity parameters, particularly b-value (rock fragility) and a-value (seismicity index) in the Maluku region before and after the 2019 Ambon earthquake. This study also aims to see whether there are changes in Peak Ground Acceleration (PGA) values for the Maluku region after the 2019 Ambon Earthquake. The seismic data used in this study comes from the USGS catalogue recorded from 2000 to 2022. The results of this study show that the b-Value of the Maluku region as a whole before the earthquake was 1.15 and decreased to 0.91 after the 2019 Ambon earthquake. However, the a-Value and b-Value for each seismic source zone increased. In addition, the PGA value for the Maluku region is 1.25g. These results provide the conclusion that the Maluku region is included in the zone with medium seismic hazard with the level of earthquake damage included in category VI of the MMI scale.